2020
DOI: 10.1002/csr.1955
|View full text |Cite
|
Sign up to set email alerts
|

The search for alignment of board gender diversity, the adoption of environmental management systems, and the association with firm performance in Asian firms

Abstract: This study examines how board gender diversity can address the challenges to adopt environment management systems (EMS) to improve firm performance. Firstly, drawing on gender socialization and diversity theories, higher board gender diversity motivates firms to adopt EMS. Empirical evidence shows that firms with gender diverse boards are greener. Secondly, the study investigates the maxim that green pays to be green. The empirical findings highlight a positive and statistically significant but economically mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 113 publications
1
27
2
Order By: Relevance
“…At the same time, we found that CSR performance also amplifies the negative relation between ROA and probability of CEO turnover. Through CSR, a CEO sends a message to the larger community that he recognizes its position in helping society and is acting upon that acknowledgment (Rehman et al, 2020). At the second stage, we found that gender critical mass moderates the negative relation between firm performance (ROA and CSR) and CEO turnover in an Asian context.…”
Section: Discussion Of Main Findingsmentioning
confidence: 77%
See 3 more Smart Citations
“…At the same time, we found that CSR performance also amplifies the negative relation between ROA and probability of CEO turnover. Through CSR, a CEO sends a message to the larger community that he recognizes its position in helping society and is acting upon that acknowledgment (Rehman et al, 2020). At the second stage, we found that gender critical mass moderates the negative relation between firm performance (ROA and CSR) and CEO turnover in an Asian context.…”
Section: Discussion Of Main Findingsmentioning
confidence: 77%
“…At the same time, we found that CSR performance also amplifies the negative relation between ROA and probability of CEO turnover. Through CSR, a CEO sends a message to the larger community that he recognizes its position in helping society and is acting upon that acknowledgment (Rehman et al, 2020). Our findings extend not only to the direct linkage between CSR and CEO turnover but also suggest that CSR investment successively frames the assessment of ROA provided during the CEO's term of office.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies reveal a positive relationship between the presence of female directors and sustainable activities (see e.g. Beji et al, 2020;Rehman et al, 2020;Saheed Olanrewaju et al, 2020). Female directors not only positively affect corporate sustainability, but they also play a key role in "enabling firms to ethically manage their social responsibilities and sustainable practices" (Yasser et al, 2017) and in promoting the adoption of equality, diversity and inclusion policies (Bruna et al, 2014).…”
Section: Sustainable Strategy and Activitiesmentioning
confidence: 99%